Dios me ensena como vivir : con los diez mandamientos a seguir - Mackall, Dandi Daley; Gevry, Claudine ([Grand Rapids, Mich.] : Editorial Portavoz, 2012)
This engaging title joyfully presents the message of the Ten Commandments from Exodus 20 to young children. Each commandment is portrayed with lively, colorful illustrations of familiar childhood experiences. The easy-to-understand rhyming text tells the story of how children can learn and obey the Ten Commandments.
Este atractivo titulo presenta el mensaje de los Diez Mandamientos de Exodo 20 a los ninos pequenos. Se explica cada mandamiento con ilustraciones coloridas de experiencias vividas en la infancia. El texto, facil de entender, cuenta la historia de como los ninos pueden aprender y obedecer los Diez Mandamientos.
Translation of :With ten rules to obey, God shows the way.
Keywords: Bible stories -- Juvenile literature; Ten commandments -- Juvenile literature